Diatom abundance in the polar oceans is predicted by genome size - Roberts, Wade R.; Siepielski, Adam M.; Alverson, Andrew J. (PLOS Biology, 2024)
Body size is a fundamental predictor of organismal abundance, and larger-bodied organisms predominate in colder areas ("Bergmann’s rule"). This study of diatoms reveals that in these unicellular organisms, genome size, rather than cell size, is a strong predictor of species abundance in the polar oceans.